The manifestations of political correctness in the Lithuanian and Latvian languages - Kvašytė, Regina; Maskuliūnienė, Džiuljeta; Župerka, Kazimieras Romualdas (Lietuvių kalba, 2019)
The article discusses the manifestations of the ideology of political correctness in the current Lithuanian and Latvian languages. It features a more detailed analysis of the usage of words referring to persons by health, race and nationality (invalidas – neįgalusis, invalīds – nespējnieks [invalid – disabled]; negras – juodaodis, nēģeris – melnais [negro – black]; čigonas – romas, čigāns – roms [gipsy – Romany], etc.). At first glance, the intentions of the supporters of that ideology seem honorable: their substitution for ordinary words can be seen as a euphemism of a language, which is promoted by tolerance of otherness, empathy, and the pursuit of non-offending communication. However, the implementation of that ideology introduces a new language and is often accessible to extremes, absurdity. The authors of the article agree with linguists and other cultural figures who believe that imposing political correctness for a language is essentially harmful. One characteristic consequence of this interference with language is that a certain, usually negative, connotation of the word, naturally or fancifully conceived by ideology enthusiasts in English-speaking society, is transferred to other languages irrespective of their established meanings and shades. Thus, neutral words unreasonably attribute to a negative evaluation of the subject matter. Recommendations for the usage of words in one way or another should be guided by linguistic science and one’s own cultural tradition, not by an unconditional adherence to any ideology.